2007
DOI: 10.1007/s00428-007-0506-4
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 localization within plasma membrane caveolae-like structures in human lobular intraepithelial neoplasia of the breast

Abstract: Cyclooxygenase-2 (COX-2) is highly expressed in human intraepithelial neoplasia of the breast and takes part in the molecular pathway implicated in progression of breast cancer. Recently, we demonstrated that COX-2 protein is mainly located in plasma membrane of lobular intraepithelial neoplasia (LIN) cells suggesting a localization in caveolae-like structures. The aim of the present study is to establish subcellular locations of COX-2 and its colocalization with caveolin-1 (CAV-1) to caveolae structures in LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In primary lobular and ductal mammary tumors, COX-2 is present in plasma-membrane caveolae and cytosol, respectively [39], without the nuclear and perinuclear localization observed by us in bone metastasis.…”
Section: Discussionmentioning
confidence: 53%
“…In primary lobular and ductal mammary tumors, COX-2 is present in plasma-membrane caveolae and cytosol, respectively [39], without the nuclear and perinuclear localization observed by us in bone metastasis.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, our group recently demonstrated the expression of Cav-1 protein in a large portion of human lobular intraepithelial neoplasia of the breast. 21 Analysing Cav-1 expression in these three population, no significant differences were found between lobular intraepithelial neoplasia lesion with and without invasive component and between invasive lobular carcinoma with and without lobular intraepithelial neoplasia component. These data suggest that, at least for Cav-1, there is no association between Cav-1 expression in lobular intraepithelial neoplasia lesion and in the adjacent invasive lobular carcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…This antibody has been used and validated previously by our group and by others. 21,23,24 Sections were incubated with LSAB2 (Dakocytomation). 3-3 0 -diaminobenzidine was used for colour development and haematoxylin was used for counterstaining.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have investigated the possibility that FYN, found in complex with COX2, is capable to regulate the enzyme activity. Since it has been reported that COX2 and FYN both are localized in caveolae like structures in some cancer cells [36, 37], it is possible that caveolae is one of cellular comparmtent where FYN is capable to regulate COX2 activity.…”
Section: Resultsmentioning
confidence: 99%